“I Wouldn't Have Asked for Help if I had to go to the Library”: Reference Services On Site - Jennifer Lee; K. Alix Hayden; Don MacMillan (Issues in Science and Technology Librarianship)
Students may be reluctant to ask questions at a library reference desk because it is such a public venue. It may be possible to give them an alternative by providing reference services outside of the library within a faculty lab or office. Advantages include convenience and proximity to students, faculty, and their learning communities. The service may also foster closer and stronger relationships with departments. It is important to choose a location wisely, as well as advertise widely. This paper examines the provision of reference services outside of the traditional library environment, and describes two initiatives involving librarians for the Faculty of Nursing and the Faculty of Science at the University of Calgary.